2016
DOI: 10.3892/mmr.2016.5470
|View full text |Cite
|
Sign up to set email alerts
|

Increased protein expression levels of pCREB, BDNF and SDF-1/CXCR4 in the hippocampus may be associated with enhanced neurogenesis induced by environmental enrichment

Abstract: Brain plasticity is very sensitive to the environment. Certain neurotrophic factors and neurotransmitter receptors, including brain-derived neurotrophic factor (BDNF), cyclic adenosine monophosphate response element‑binding protein (CREB), stromal cell‑derived factor‑1 (SDF‑1) and its specific receptor, C-X-C motif chemokine receptor 4 (CXCR4), are important in neurogenesis in adult animals. In the present study, the effects of environmental enrichment (EE) on neurogenesis in the dentate gyrus (DG) and subvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 47 publications
2
21
0
1
Order By: Relevance
“…Thus, it has been reported that the increase in the neurogenesis that occurs due to exposure to EE results from the integration of new functional circuits of generated neurons and an increase in the number of synapses in the perforating fiber pathway of the DG and CA3‐CA1 region (Madronal et al, ). It is now clear that the exposure of adult rats to EE and exercise induces neurogenesis in the DG and may be correlated with an elevation in hippocampal BDNF levels (Choi et al, ; Mosaferi, Babri, Mohaddes, Khamnei, & Mesgari, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been reported that the increase in the neurogenesis that occurs due to exposure to EE results from the integration of new functional circuits of generated neurons and an increase in the number of synapses in the perforating fiber pathway of the DG and CA3‐CA1 region (Madronal et al, ). It is now clear that the exposure of adult rats to EE and exercise induces neurogenesis in the DG and may be correlated with an elevation in hippocampal BDNF levels (Choi et al, ; Mosaferi, Babri, Mohaddes, Khamnei, & Mesgari, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF was shown to stimulate the differentiation of neural progenitor cells, regulating neurogenesis 39 . Moreover, BDNF administration or its increased expression promotes hippocampal neurogenesis and increases neuronal activity 40, 41 . Therefore, BDNF not only regulates the neurons, but also promotes growth and physiological functions (steroidogenesis) in granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, available data about the CXCR4 receptor behavior are contradictory. Whereas some authors, using different models, have demonstrated that CXCR4 activation may promote reversion of cellular damage induced by several insults [6,11,34], other authors have reported the opposite [15,16,17]. In fact, the activation of CXCR4 chemokine receptor led to detrimental effects in these recent studies [14,15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to SDF-1α rescues these cells from apoptosis and induces a time-dependent increase of total Rb expression [6]. Increased expression of SDF-1α/CXCR4 in the hippocampus may be associated with enhanced neurogenesis induced by environmental enrichment [11]. AMD3100 reversed the neurogenesis and behavioral recovery promoted by forced limb-use in rats subjected to stroke [12].…”
Section: Introductionmentioning
confidence: 99%